Roadmap Strategis Penerapan Satu Data Aparatur Sipil Negara - Cahyaningsih, Elin (Universitas Komputer Indonesia, 2023)
Information Technology governance is a series of IT strategies, planning, policies, IT implementation, resources and activity control. Data governance helps organizations in the availability, usability, integrity and security of data as a valuable asset in the organization. The State Civil Service Agency as the data manager for the State Civil Service is committed to providing data-based ASN management services by providing quality ASN data that is accurate, up-to-date, integrated and accountable and easy to access and use between agencies through one ASN data. Improving the quality of ASN data, some face problems related to data completeness and accuracy, for this reason a strategy roadmap for implementing one ASN data is needed. This research uses a fishbone diagram analysis approach to identify problems, gap analysis to determine strategic steps and risk analysis to describe the risks in each strategic activity. A hybrid and synthetic approach was taken to formulate each dimension in the strategy roadmap as well as strategic steps in each dimension. The research results explain that there are nine dimensions of the roadmap strategy, namely regulations/policies, ICT human resources in the data sector, data architecture, master/reference data, data standards, metadata, databases, data quality and data interoperability. The roadmap strategy is preceded by determining the vision, mission and goals of Satu Data ASN.